(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2001)
A number of essential peculiarities of intra-annual distribution of mineralization of river waters are analyzed in the paper. The results provide that the mineralization in river waters has a precise intra-annual distribution and directly relates to water discharge. The maximal value of mineralization and the minimal runoff of drought period manifest themselves simultaneously; while the minimal value of mineralization coincides with the maximal runoff in flood period.